2015
DOI: 10.1007/s11524-015-9936-5
|View full text |Cite
|
Sign up to set email alerts
|

Community Characteristics are Associated with Blood Pressure Levels in a Racially Integrated Community

Abstract: Community problems have been associated with higher, and community resources and social cohesion with lower, blood pressure. However, prior studies have not accounted for potential confounding by residential racial segregation. This study tested associations between community characteristics and blood pressure levels and prevalent hypertension in a racially integrated community. The Exploring Health Disparities in Integrated Communities Study measured blood pressure in residents of two contiguous racially inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The findings are robust and hold independent of setting, cohort, age group, psychosocial determinants, and health outcome. Other researchers have also reported similar findings 55 - 81 (see Table 2 ).…”
Section: Unequal Gain From Equal Resources and Assetssupporting
confidence: 78%
“…The findings are robust and hold independent of setting, cohort, age group, psychosocial determinants, and health outcome. Other researchers have also reported similar findings 55 - 81 (see Table 2 ).…”
Section: Unequal Gain From Equal Resources and Assetssupporting
confidence: 78%
“…With nearly half of African Americans in the United States having some form of cardiovascular disease, (46% among men and 48% among women), they are more susceptible to experiencing frequent hospitalisations and premature death (American Heart Association, ; Cunningham et al., ). African Americans living in low‐income urban settings experience unique social challenges such as increased exposure to crime and environmental toxins, lack of resources and poor access to healthy foods in comparison with people not living in low‐income urban areas (Franco, Roux, Glass, Caballero, & Brancati, ; Gaskin et al., ; Samuel, Thorpe, Bower, & LaVeist, ). Studies and reports have highlighted prevalence, identified barriers to, and made recommendations for effective management of cardiovascular disease.…”
mentioning
confidence: 99%